PROFITABILITY RATIO ANALYSIS FOR MEASURING FINANCIAL PERFORMANCE IN ASSETS IN SHARIA BANKING COMPANIES IN INDONESIA PERIOD 2018-2022 - Riza Lailatul Aulidiah; Fida Oktafiani (SEAN Institute, 2023)
The purpose of this study was to better understand how Indonesian Islamic banking companies' assets and financial performance would be measured using profitability ratio analysis between 2018 and 2022. The asset growth rate of Indonesian Islamic banking businesses is estimated in this study using the variables gross profit margin (GPM), net profit margin (NPM), return on investment (ROA), and return on investment (ROE). Pick a side. The data in this study are regularly distributed, according to observations. Both the multicollinearity and normalcy tests turned up no abnormal variables. The autocorrelation test, on the other hand, confirmed that there is autocorrelation. The study's findings, however, can still be used to support multiple linear regression equation models. As the significance level is above 0.05, the findings of this study indicate that neither the gross GPM nor the NPM variables have a significant influence on wealth growth. However, because their significance levels are smaller than 0.05, the variables ROA and ROE have a bigger influence on wealth growth. Because the significance level is smaller than 0.05, all four variables— GPM, NPM,ROA and ROE, are simultaneously significant to wealth growth. if it is a factor. Forecasting skills for the interdependent 19.8% asset variables NPM,ROA and ROE.